Resection of deep-infiltrating endometriosis could be a risk factor for uterine rupture: a case series with review of the literature - Hanane Ziadeh, M.D; Pierre Panel, M.D; Arnaud Letohic, M.D; Michel Canis, M.D., Ph.D; Sarah Amari, M.D; Tristan Gauthier, M.D., Ph.D; Julien Niro, M.D (Elsevier, 2020)
Objective: To highlight the possible correlation between deep-infiltrating endometriosis (DIE) resection and subsequent uterine rupture. Design: Case series and review of the literature. Setting: Endometriosis referral hospitals. Patient(s): Seven young women who underwent laparoscopic resection of DIE, six of whom had uterine rupture before or during labor; the seventh patient had a posterior wall defect that placed her at increased risk of future uterine rupture. Intervention(s): Diagnosis of uterine rupture before or during labor in patients with a history of prior resection of DIE, leading to delivery by emergency delivery section or emergency laparotomy for exploration and repair. Main Outcome Measure(s): Immediate neonate and maternal salvaging caesarean delivery or laparotomy followed by surgical correction of the rupture. Result(s): As of 2019, no publications in the literature had considered uterine rupture among the obstetric complications of endometriosis. The reporting of such findings is crucial because of the increase in surgical management of endometriosis. We report seven cases of uterine rupture in pregnancy in women who had undergone resection of DIE. In six patients, surgeons found uterine rupture at the level of the previous resected endometriosis and diagnosed a posterior wall defect at the same level in one patient. Conclusion(s): Our case series sheds light on the potential increased risk of uterine rupture during pregnancy among women who have had a prior resection of DIE. In future, if these patients are considered high-risk pregnancy cases, their care should be managed by high-risk obstetric specialists.